Abóbora como cultura energética em codigestão anaeróbia com água residuária da suinocultura: análise de viabilidade técnica e financeira - Pereira, Edilene da Silva (2024)
The use of Energy Crops (EC) in Anaerobic Codigestion (CoDA) with organic waste from confined animal production systems provides greater energy potential through the generation of biogas/methane and a biofertilizer richer in nutrients, meeting the premises of the circular economy. The aim of this study was to compare the following treatments: monodigestion of ARS (T0), co-digestion of ARS and raw dried squash (T1), co-digestion of ARS and cooked dried squash (T2), co-digestion of ARS and raw strawberry squash (T3), and co-digestion of ARS and cooked strawberry squash (T4). To this end, Methane Production Potential (MPP) tests were carried out in accordance with the German Standard VDI-4630 and in bench biodigesters with semi-continuous feeding, which monitored the specific production of biogas and methane and the series of solids. In the PPM trials, kinetic analysis was carried out using the Modified Gompertz, Cone, Modified First Order, Logistic and Modified Logistic models and, in the trial with semi-continuous feeding, the parameters of pH, total alkalinity (TA), volatile acidity (VA), agronomic quality of the biofertilizer and germination index (GI) were determined. The results obtained defined full-scale scenarios for agro-industrial cooperatives, with an assessment of financial viability. The results of the specific biogas and methane production of T3, from the PPM trials, were statistically higher than the other treatments. From the kinetic analysis, the Cone model showed a better fit of the metrics and, due to the increase in biogas in T3, its specific yields were higher. These results were confirmed by the test with semicontinuous feeding, which showed a higher yield of biogas (1025.9L.kgSV-1) and methane (1025.9L.kgSV-1), as well as an increase in specific production of 22.2% and 26.8%, respectively, in T3 compared to T0. T3 was also responsible for the highest concentration of volatile fatty acids (VFAs) - 1,516.8mg.L-1 VA - and the best VA/VA ratio - 0.3. The concentrations of nitrogen, phosphorus and potassium increased in the biofertilizer in all treatments, revealing the efficiency of the conversions, suggesting biofertilizer for fertigation in crops as an interesting alternative from the point of view of agronomic valuation and nutritional recycling. With a Net Present Value of R$1,717.82, an Internal Rate of Return of 30.5%, a Profitability Index of 1.98 and a discounted Payback of 3.68, T3 was the only scenario that showed financial viability, overcoming investment risks in time, with liquidity and a surplus.